GE_GERICHTE P/758/2012 vom 11. Juni 2012 - GE Cour de justice (2012)
DIFFAMATION; PREUVE LIBÉRATOIRE; COMPÉTENCE; DÉPENS; ASSISTANCE JUDICIAIRE | CPP.310; CPP.8; CPP.343; CPP.436; CP.14; CP.173; CPP.136